Analisis Yuridis Gugatan Uni Eropa ke World Trade Organization terhadap Indonesia akibat Regulasi dan Kebijakan Pembatasan Ekspor Bijih Nikel (SETARA : Jurnal Ilmu Hukum, 2024)
This article examines the European Union's legal challenge at the World Trade Organization against Indonesia's restrictions on exports of low-grade nickel ore. The issue is important because Indonesia's downstream policy seeks to increase domestic value added and preserve strategic mineral reserves, while the European Union views the restrictions as inconsistent with multilateral trade obligations. Using normative juridical research, the article reviews Indonesian mining regulations, relevant WTO instruments, and doctrinal writings on international trade law. The study finds that the dispute centres on Indonesia's export restrictions and domestic processing policy, which the European Union argues conflict with the General Agreement on Tariffs and Trade 1994 and the Agreement on Subsidies and Countervailing Measures. At the same time, Indonesia frames the policy as part of its sovereign authority to manage natural resources for national welfare and industrial development. The article concludes that the dispute has both legal and economic implications, including tension in bilateral trade relations, pressure on Indonesia's hilirisasi agenda, and the need for clearer alignment between domestic resource governance and international trade commitments.